(untitled) (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2015)
The choice of oil pollution dispute resolution by Tanker Ship in national marine law system is highly important to be analyzed in-depth concerning the choice of oil pollution dispute resolution by Tanker Ship in Indonesia is resolved in peaceful manner based on the principle of polluter pays principle. The dispute resolution choice in peace is amended by the internationalinstrument ofUNCLOS in article 279 which is, in Indonesianpositive law system, generated through several national legal instruments. Furthermore, the dispute resolution choice is such an important thing considering the purposes of marine environment protection by the coastal states through the law enforcement of sovereign coastal states. The consequence of dispute resolutionchoice with the concept of ecocracy and sustainable environmental development, in line with the reconstructive purpose of philosophical approach of environmental problem settlement through the concept of ecocracy and the paradigm of deep ecology and green constitution, itis expected to be able to be included in national legal system withe law enforcers who understand ecoliteracy